On Exploration of Challenges Faced by Green Finance, Sustainable Finance, Health Finance and Embedded Finance and Hierarchical Inter-relationships Amongst them - Jyotin Jauhar; Remica Aggarwal (Contemporary Research in Business, Management and Economics Vol. 7, 2024)
Moving to a low-carbon or green economy would need extraordinary levels of fresh capital investment, notably in the form of green financing, to support activities that cut GHG emissions and assist firms in adapting to the effects of climate change. Sustainable finance refers to financial tools that serve environmental and social goals, green finance is entirely concerned with environmental objectives. This research work therefore compares the four categories of financing i.e. green finance; sustainable finance, health finance and embedded finance and the associated challenges. It thereafter studies the hierarchical inter-relationships amongst them using VAXO based matrices of ISM methodology.